Sperm Detection in Congenital Ejaculatory Duct Cyst Repair: A Case Report - Ahmad Ricardo Silalahi (Journal of Global Pharma Technology, 2019)
Ejaculatory duct cyst is a very rare case. We report a 26-year-old man with primary infertility complaining of aspermia since before marriage, precisely since the first wet dream. General physical examination and hormonal levels were in normal values. The cyst was visualized through abdominal TRUS, MRI and abdominal ultrasound (USG). The sperm detection test was performed before and after repaired by TURED. Before repair, the sperm was absent at Cowper’s gland secretion, post orgasmic urine and post massage prostate. After repair, sperm was detected in cyst aspiration fluid and useful to distinguish ED cyst between the Mullerian duct and utriculus cyst. In addition, after one month post repaired, the sperm concentration, motility and morphology increased. The improvement of sperm quality is useful to determine the infertility program whether IVF, IUI or natural pregnancy.Keywords: Ejaculatory duct cyst, Male infertility, Sperm detection.